Persuasive Messaging: Millennials’ Perceptions Of Instagram dvertising Of The ‘Jenius Connect’ Payment System - Mutiara, Hanjani Deandri; Putri, Andintia Wijayanti; Octavian, Alexander (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Payment systems have become the most often used by many people in the world. Technology advances have encouraged people in using cashless terms through credit cards, debit cards, and e-money. Meanwhile, the subject of this research is Jenius. Jenius is a revolutionary banking application that is equipped with a visa debit card to help people conduct their financial activities such as saving, transacting, or managing people’s finances to be more safe, smart, and simple. Everything is done from one place including all on a smartphone by using the Jenius mobile application. This research has a focus on the perception of millennials towards the persuasive message of Jenius Connect advertising on Instagram as a payment system. The theory that is used is Elaboration Likelihood Model (ELM), Computer-Mediated Communication (CMC), and Integrated Marketing Communication (IMC). There are several concepts which are Instagram, Instagram Advertising, and Digital Marketing. The research methodology is using qualitative data collection through observation and interview. The finding of the research has stated that most Millennials tend to like the promos that are offered in the Instagram account of Jenius. Besides, the findings of this research update the ELM from the point of view of millennials that ELM has contributed to quick decisions or peripheral routes since the advent of the internet and social media.